Flexible contact material and preparation method thereof, and air electrode connection structure and preparation method thereof
By using flexible contact materials in solid oxide batteries, the spinel-shaped structure is generated by the oxidation reaction of the flexible metal frame and the deposited layer, which solves the problem of thermal expansion mismatch of rigid connecting materials and achieves the improvement of high-temperature conductivity and long-term stability.
Patent Information
- Application Number
- CN202411874484.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-18
AI Technical Summary
In existing solid oxide batteries, the rigid connecting material does not match the thermal expansion coefficient of the air electrode and the connector, resulting in contact failure and the application amount is difficult to grasp, affecting the electron conduction resistance and battery performance.
A flexible contact material, including a flexible metal frame and a deposition layer, is used to coat the deposited layer on the surface of the flexible metal frame by electrodeposition method, and an oxidation reaction is carried out under a high-temperature oxidation atmosphere to form a spinel-shaped structure as a contact layer.
It achieves good high-temperature conductivity and long-term operation stability, reduces plane resistance, improves the current transmission efficiency of the battery, and adapts to the thermal expansion differences of adjacent materials.
Smart Images

Figure CN119742391A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of solid oxide batteries, and in particular to a flexible contact material and a preparation method thereof, an air electrode connection structure and a preparation method thereof, a solid oxide battery and a battery stack. Background Art
[0002] Solid oxide cells (SOC) are usually divided into solid oxide fuel cells (SOFC) and solid oxide electrolysis cells (SOEC) according to their working modes, both of which include three parts: fuel electrode, electrolyte and air electrode. Among them, SOFC is an all-solid-state energy conversion device that can efficiently convert chemical energy in fuels such as hydrogen, ammonia or hydrocarbons directly into electrical energy. It is a very promising power generation technology. In recent years, considering the increasingly severe environmental problems, countries around the world have also invested a lot of research funds and manpower in SOEC, the reverse working mode of SOFC. In this way, the same set of equipment can use renewable electricity to absorb carbon dioxide and produce synthesis gas and carbon-containing chemicals.
[0003] SOC is similar to electrochemical devices such as proton exchange membrane fuel cells and alkaline water electrolyzers. In order to achieve a higher voltage and power, the battery stack must use a connector to connect multiple batteries in series. Each connector is connected to the fuel electrode and air electrode of two adjacent batteries. For example, SOFC technology mainly adopts a flat stack structure with an operating temperature of approximately 600-900°C. In order to achieve good contact between the connector and the electrodes on both sides and reduce the resistance to electron conduction, it is usually necessary to add a layer of contact material between the electrode and the connector that can fit tightly on both sides and has good conductivity at high temperatures. Nickel mesh or nickel foam material is currently used as the contact layer on the fuel electrode side, but because the air electrode is in a high-temperature oxidizing atmosphere, metal materials cannot be directly used as the contact layer.
[0004] At present, most rigid connection materials are used as contact materials. For example, patent CN103427092A proposes a composite conductive ceramic material with a spinel structure phase encapsulating a perovskite structure phase. When used as a cathode contact layer, it can simultaneously exhibit the low-temperature sintering activity of the spinel material and the high conductivity of the perovskite phase. It can achieve good bonding with the cathode and the connector at 900°C or even lower temperatures, and maintain a resistance of less than 20mΩ·cm in the SOFC working environment. 2 However, this method requires the use of a sol-gel method to prepare two different ceramic powders, which also involves multiple calcinations and ball milling, and the production process is complex and the production cycle is long.
[0005] Patent CN116404188A proposes a LaNi 0.6 Fe 0.4 O3 contact layer material particle size control method and application. Through simple high-temperature calcination and screen screening, the invention can achieve controllable adjustment of LaNi in the range of 1 to 10 μm. 0.6 Fe 0.4 The average particle size of the O3 contact layer material particles. The powder is used as the cathode contact layer by slurry coating. The rigid connection formed has a large porosity and low powder sintering activity, which is conducive to gas transmission, but the overall conductivity is relatively general, and the resistance is mostly 50mΩ·cm 2 above.
[0006] Patent CN117334943A proposes a method of forming a slurry of lanthanum strontium manganese oxide on the cathode of SOFC, and then sintering it during the test to form a lanthanum strontium manganese oxide contact layer. The contact layer prepared by this method still needs to control the particle size of lanthanum strontium manganese ceramic particles, as well as the composition ratio of pore formers, binders and solvents; in addition, the thickness of the formed contact layer embryo needs to be adjusted, and the contact layer pressed on the cathode covers more electrode area, affecting the performance of the battery.
[0007] However, the thermal expansion coefficient of the rigid connection material does not match that of the air electrode and the connector, and the adaptability to the deformation of the adjacent materials is poor, which is prone to cracking and contact failure. In addition, the application amount of the rigid connection material is difficult to control. Too much is easy to block the porous structure of the electrode, and too little will increase the resistance to electronic conduction. When using the rigid connection material as a contact layer, a balance must be made between sintering activity and conductivity so that it can be sintered firmly at the SOFC operating temperature and have good conductivity. This has resulted in a limited application range of rigid materials. Once the connector or battery material is replaced, it is very likely that the original contact material will become unsuitable.
[0008] Based on this, there is a new type of contact material. For example, patent CN103887533A provides a high-conductivity solid oxide fuel cell flexible connection component, which is prepared by coating one or more layers of coating material on the surface of an alloy mesh or foam body to form a flexible connection component with high conductivity in a high-temperature oxidizing atmosphere. The obtained connector component has high conductivity, high-temperature oxidation resistance, and flexibility. The preparation method of this high-temperature connection component: the coating material is applied to the surface of the alloy mesh or foam body component by brushing, spraying or dipping, and sintered in a low temperature range of 700-900°C to form a coating. However, most of these connection components are formed into a contact layer embryo by slurry coating. The bonding force between the coating material and the substrate in the contact layer after sintering is difficult to grasp, and the stability of the contact layer after long-term operation is poor. Summary of the invention
[0009] In order to solve the above technical problems, the present invention provides a flexible contact material and a preparation method thereof, an air electrode connection structure and a preparation method thereof, a solid oxide battery and a battery stack.
[0010] In a first aspect, an embodiment of the present invention discloses a flexible contact material for use between an air electrode and a connector of a solid oxide battery, comprising a flexible metal skeleton and a deposition layer, wherein:
[0011] The flexible metal skeleton is selected from one or more of Fe, Co, Ni, Cu and Mn, the deposited layer is coated on the surface of the flexible metal skeleton, the deposited layer includes one or more of Fe, Co, Ni, Cu and Mn, the composition of the flexible metal skeleton and the composition of the deposited layer are not completely the same, the deposited layer in the flexible contact material can be oxidized with the flexible metal skeleton in an atmosphere containing oxygen and in a heated state to generate a general formula A x B 3-x O4 (1≤x≤2) spinel structure, the spinel structure is coated on the surface of the flexible metal skeleton, wherein A is the component of the flexible metal skeleton, B is the component of the deposition layer, and 1≤x≤2.
[0012] By adopting the above technical scheme, the flexible metal skeleton and the deposited layer can be oxidized in an oxygen atmosphere during the air electrode reaction to generate a contact layer with a spinel structure, thereby making the contact layer have good high-temperature conductivity and long-term operation stability.
[0013] According to another specific embodiment of the present invention, the deposited layer further includes one or more of La, Ce and Y.
[0014] According to another specific embodiment of the present invention, the thickness of the flexible metal skeleton is 50-500 μm.
[0015] According to another specific embodiment of the present invention, the pore size of the flexible metal skeleton is 40 to 1800 μm.
[0016] According to another specific embodiment of the present invention, the mass of the deposited layer accounts for 5-10 wt % of the total mass of the flexible contact material.
[0017] In a second aspect, an embodiment of the present invention further discloses a method for preparing a flexible contact material, which is used to prepare the flexible contact material in any embodiment of the first aspect, comprising the following steps:
[0018] Electrodeposition: immersing the flexible metal skeleton in an electrolyte for electrodeposition to obtain the flexible contact material;
[0019] Wherein, the electrolyte includes an acid salt and water, and the acid salt is an acid salt corresponding to the components of the deposition layer.
[0020] By adopting the above technical solution, the deposition layer can be coated on the surface of the flexible metal skeleton by electrodeposition, which is conducive to regulating the deposition amount and uniformity of the deposition layer, and can ensure the strong bonding force between the deposition layer and the flexible metal skeleton, thereby improving the overall stability of the flexible contact material.
[0021] According to another specific embodiment of the present invention, the acid salt includes acid ions, and the acid ions are sulfate or chloride ions.
[0022] According to another specific embodiment of the present invention, the electrolyte further includes a second acid salt, the second acid salt has the same acid radical ion as the acid salt, and the cation in the second acid salt is an alkali metal ion.
[0023] According to another specific embodiment of the present invention, the electrolyte further includes an additive, and the additive is one of pyrophosphate, citrate, ammonium sulfate or boric acid.
[0024] According to another specific embodiment of the present invention, the pH value of the electrolyte is 4-7.
[0025] According to another specific embodiment of the present invention, in the electrodeposition step, the electrodeposition is pulse electrodeposition, and the pulse current density of the pulse electrodeposition is 10 to 100 mA / cm 2 , the pulse frequency is 1 to 100 Hz, the deposition time is 1 to 60 minutes, and the duty cycle is 20 to 80%.
[0026] In a third aspect, an embodiment of the present invention discloses an air electrode connection structure for a solid oxide battery, comprising an air electrode, a contact layer and a connector arranged in sequence, wherein the contact layer is obtained by an oxidation reaction of the flexible contact material in any embodiment of the first aspect, wherein the oxidation reaction is that the deposited layer reacts with the flexible metal skeleton under an atmosphere containing oxygen and under a heating state to generate a general formula A x B 3-x A spinel structure of O4 (1≤x≤2), wherein the spinel structure is coated on the surface of the flexible metal skeleton, wherein A is the component of the flexible metal skeleton, B is the component of the deposition layer, and 1≤x≤2.
[0027] By adopting the above technical solution, a good interface contact can be formed with the connector 3 and the air electrode 1, thereby reducing the surface resistance and improving the current transmission efficiency of the battery.
[0028] According to another specific embodiment of the present invention, the air electrode connection structure is connected to the surface resistance test device to form a loop, and a current is passed through the constant current density of 500 mA / cm 2 , in air atmosphere, after isothermal operation at 850°C for 300h, after 20 cooling-heating cycles, the surface resistance of the air electrode connection structure is tested to be ≤50mΩ·cm 2 , wherein the cooling-heating is a process of cooling from 850°C to 200°C, then heating from 200°C to 850°C and continuously operating at 850°C for 10 hours.
[0029] In a fourth aspect, an embodiment of the present invention discloses a method for preparing an air electrode connection structure, which is used to prepare the air electrode connection structure in any embodiment of the third aspect, comprising the following steps:
[0030] Electrodeposition: immersing the flexible metal skeleton in an electrolyte for electrodeposition to obtain the flexible contact material;
[0031] Preparing the air electrode connection structure: after assembling the air electrode, the flexible contact material and the connector, the deposited layer and the flexible metal skeleton undergo an oxidation reaction under an oxygen-containing atmosphere and a heating state to obtain the contact layer, thereby obtaining the air electrode connection structure;
[0032] Wherein, the electrolyte includes an acid salt and water, and the acid salt is an acid salt corresponding to the components of the deposition layer.
[0033] By adopting the above technical solution, it is possible to achieve good bonding with adjacent components while exhibiting good high-temperature conductivity and long-term operating stability, and the preparation method is simple and feasible.
[0034] According to another specific embodiment of the present invention, the heating temperature of the heating state is 800-1000°C.
[0035] According to another specific embodiment of the present invention, in the step of preparing the air electrode connection structure, the air electrode, the flexible contact material and the connector are assembled and then sintered so that the deposited layer and the flexible metal skeleton undergo an oxidation reaction to generate the contact layer, thereby obtaining the air electrode connection structure.
[0036] According to another specific embodiment of the present invention, in the step of preparing the air electrode connection structure, the air electrode, the flexible contact material and the connector are assembled into a solid oxide battery, the solid oxide battery is started and the solid oxide battery reaches the operating temperature, so that the deposition layer and the flexible metal skeleton undergo an oxidation reaction to generate the contact layer, thereby obtaining the air electrode connection structure.
[0037] In a fifth aspect, an embodiment of the present invention discloses a solid oxide battery, comprising an air electrode connection structure as in any embodiment of the third aspect, or comprising an air electrode connection structure obtained by the preparation method as in any embodiment of the fourth aspect.
[0038] The above technical solution can improve the conductivity between the air electrode and the connector of the solid oxide battery, which is beneficial to improving the long-term stable operation performance and allowing more current to be transmitted under the same voltage, thereby improving the current collection efficiency of the solid oxide battery.
[0039] In a sixth aspect, an embodiment of the present invention discloses a battery stack, comprising a solid oxide battery as in any embodiment of the fifth aspect.
[0040] By adopting the above technical solution, the conductivity between adjacent solid oxide cells in the battery stack can be improved so that more current can be transmitted under the same voltage, thereby improving the current collection efficiency of the battery stack, which is beneficial to improving the operating efficiency and long-term stable operation of the battery stack. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 A schematic diagram showing an air electrode connection structure according to an embodiment of the present invention;
[0042] Figure 2 The ASR data of the air electrode connection structure prepared by the comparative example of the present invention and Examples 1 to 6 are compared under air atmosphere and kept at 850° C. for 100 hours;
[0043] Figure 3 A real picture of the flexible metal skeleton under a microscope is shown in Example 2 of the present invention;
[0044] Figure 4 A physical picture of the flexible contact material of Example 2 of the present invention under a microscope is shown;
[0045] Figure 5 A scanning electron microscope image of the flexible contact material of Example 3 of the present invention is shown;
[0046] Figure 6 A scanning electron microscope image of the contact layer of Example 3 of the present invention is shown;
[0047] Figure 7 The ASR curves of the air electrode connection structures of Examples 4 and 5 of the present invention are shown in an air atmosphere, kept at 850° C. for 300 hours, and then subjected to 20 heating-cooling cycles between 200-850° C.;
[0048] Figure 8 The XRD diagram of the flexible contact material of Example 4 of the present invention after being kept at 850° C. for 50 hours in an air atmosphere is shown;
[0049] Fig. 9 The XRD diagram of the flexible contact material of Example 6 of the present invention after being kept at 850° C. for 50 hours in an air atmosphere is shown;
[0050] Fig.10 The performance of the battery stack of Example 7 of the present invention is shown Figure 1 ;
[0051] Fig.11 The performance of the battery stack of Example 7 of the present invention is shown Figure 2 .
[0052] 0. Air electrode connection structure, 1. Air electrode, 2. Contact layer, 3. Connector DETAILED DESCRIPTION
[0053] The following specific embodiments illustrate the implementation of the present invention, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. Although the description of the present invention will be introduced in conjunction with the preferred embodiment, this does not mean that the features of this invention are limited to this implementation. On the contrary, the purpose of introducing the invention in conjunction with the implementation is to cover other options or modifications that may extend based on the claims of the present invention. In order to provide a deep understanding of the present invention, the following description will include many specific details. The present invention can also be implemented without using these details. In addition, in order to avoid confusion or blurring the focus of the present invention, some specific details will be omitted in the description. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
[0054] It should be noted that in this specification, similar reference numerals and letters denote similar items in the following drawings, and therefore, once an item is defined in one drawing, it does not need to be further defined and explained in the subsequent drawings.
[0055] The terms “first”, “second”, etc. are only used for distinguishing descriptions and should not be understood as indicating or implying relative importance.
[0056] In the description of this embodiment, it is also necessary to explain that, unless otherwise clearly specified and limited, the terms "set", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in this embodiment can be understood according to specific circumstances.
[0057] In order to make the objectives, technical solutions and advantages of the present invention more clear, the embodiments of the present invention will be further described in detail below with reference to the accompanying drawings.
[0058] In the embodiment of the present invention, the air electrode is also the cathode. In SOFC, the air electrode is responsible for the reduction reaction of oxygen, and oxygen molecules gain electrons and are converted into oxygen ions. In SOEC, the air electrode is the place where oxygen is precipitated, and oxygen ions lose electrons to generate oxygen, and an oxidation reaction occurs.
[0059] In the embodiments of the present invention, the connector refers to a component used to ensure good contact between electrodes of two adjacent batteries.
[0060] In an embodiment of the present invention, the air electrode, the contact layer and the connector are sequentially attached to form a sandwich structure.
[0061] In a first aspect, the embodiments of the present invention disclose a flexible contact material, Figure 1 As shown, it is used between the air electrode 1 and the connector 3 of the solid oxide battery, that is, between the air electrode 1 and the connector 3 in the solid oxide fuel cell or the solid oxide electrolyzer. The flexible contact material includes a flexible metal skeleton and a deposition layer. In an embodiment of the present invention, the flexible metal skeleton refers to a metal material with a porosity greater than 0 and good deformation ability, and the structure of the flexible metal skeleton is, for example, cloth, mesh, felt or foam.
[0062] Among them, the flexible metal skeleton is selected from one or more of Fe, Co, Ni, Cu and Mn. That is, the flexible metal skeleton is selected from one or more of metal iron, cobalt, nickel, copper and manganese. Compared with traditional rigid connection materials, the flexible design of the flexible metal skeleton significantly improves the reliability and life of the battery. The flexible metal skeleton is selected from one or more of Fe, Co, Ni, Cu and Mn. These metal elements have multiple valence states, which are conducive to reacting to form different types of spinel structures.
[0063] The deposition layer is coated on the surface of the flexible metal skeleton, and the deposition layer includes one or more of Fe, Co, Ni, Cu and Mn, that is, the deposition layer includes one or more of iron, cobalt, nickel, copper and manganese. For example, the deposition layer is iron, the deposition layer is cobalt, the deposition layer is nickel, the deposition layer is copper, the deposition layer is manganese, the deposition layer is manganese and cobalt, or the deposition layer is a cobalt-manganese alloy. Combined with the design of the above-mentioned flexible metal skeleton, the flexible contact material itself is endowed with electrical conductivity and excellent deformation ability, so that the flexible contact material can effectively adapt to the microscopic deformation and thermal expansion difference between the air electrode 1 and the connector 3, which is beneficial to avoid cracking of the contact layer 2 and failure of contact with adjacent components, thereby facilitating stability during long-term operation.
[0064] The composition of the flexible metal skeleton and the composition of the deposited layer are not completely the same, that is, the composition of the flexible metal skeleton and the composition of the deposited layer are only partially the same, but not completely the same, or the composition of the flexible metal skeleton and the composition of the deposited layer are completely different. Specifically, for example, when the flexible metal skeleton is metal Fe, the deposited layer can be Fe and Co; when the flexible metal skeleton is metal Fe, Co, Ni, Cu and Mn, the deposited layer can be an alloy or mixture formed by Fe, Co, Ni and Cu. As a result, it is beneficial for the flexible metal skeleton and the deposited layer to react to form a spinel structure. The spinel structure exhibits semiconductor properties at high temperatures, so it has good electronic conductivity and can effectively conduct current. In addition, the spinel structure is not easy to corrode and degrade in a strong acidic or alkaline environment, has good thermal stability at high temperatures, has good interface compatibility, and has high mechanical strength to withstand external forces and thermal stresses, thereby ensuring stable operation of the battery and improving the working efficiency of the solid oxide battery.
[0065] In the above embodiment, combined with Figure 1 As shown, the deposited layer in the flexible contact material can undergo oxidation reaction with the flexible metal skeleton in an atmosphere containing oxygen and under heating to generate a general formula A x B 3-x O4 (1≤x≤2) spinel structure, the spinel structure is coated on the surface of the flexible metal skeleton, so as to be used as the contact layer 2 between the air electrode 1 and the connector 3 of the solid oxide battery. The heating state refers to heating to the oxidation temperature required for the deposition layer and the flexible metal skeleton to undergo an oxidation reaction, and the oxidation temperature is, for example, 800-1000°C. A is the composition of the flexible metal skeleton, B is the composition of the deposition layer, and 1≤x≤2. For example, when the flexible metal skeleton is metal Fe, the deposition layer can be Ni and Co, and the deposition layer and the flexible metal skeleton generate a general formula of Fe x (NiCo) 3-x O4 spinel structure, 1≤x≤2.
[0066] Preferably, when the flexible metal skeleton is metal Mn, the deposited layer is Cu, and the general formula of the deposited layer and the flexible metal skeleton is Mn x (Cu) 3-xO4 spinel structure, 1≤x≤2. The inventors have found through research that the spinel structure has good conductivity at higher temperatures, and the reason is due to the "small polaron jumping" mechanism. Simply put, for this type of ionic crystal, the electron-lattice coupling is enhanced at high temperature to form small polarons. Small polarons participate in conduction by jumping between lattices, and their conductivity is affected by factors such as mixed valence bands and oxygen vacancy concentrations. Among them, a small polaron refers to a polaron whose size is equivalent to the lattice constant, and the size of the polaron depends on the scale of the lattice polarization region where electron (or hole) coupling occurs. Among the optional elements Fe, Co, Ni, Cu and Mn in the flexible metal skeleton, the Mn element has a rich valence state (for example, a valence state of +2, +3 or +4), so that the spinel structure formed by it has more mixed valence bands, which is more conducive to charge transfer and exhibits higher conductivity. The Cu element in the deposited layer has a lower +1 valence state, which makes it easier to introduce oxygen vacancies between the lattices, promote the charge transfer between oxygen and metal atoms, increase the electron density, accelerate the migration of carriers, and enhance the conductivity. Therefore, the manganese copper spinel series composed of Mn elements and Cu elements in various valence states usually has better conductivity, that is, lower surface resistance.
[0067] The deposited layer in the flexible contact material can undergo an oxidation reaction with the flexible metal skeleton in an atmosphere containing oxygen and in a heated state. The atmosphere containing oxygen is, for example, an air atmosphere or an oxygen atmosphere. Specifically, in SOFC, the deposited layer in the flexible contact material can undergo an oxidation reaction with the flexible metal skeleton in an atmosphere containing oxygen and in a heated state to generate a contact layer 2 having a spinel structure. In SOEC, the deposited layer in the flexible contact material can undergo an oxidation reaction with the flexible metal skeleton in an atmosphere containing oxygen and in a heated state to generate a contact layer 2 having a spinel structure. More specifically, the oxidation reaction of the flexible metal skeleton and the deposited layer occurs at a position where three phases of the flexible metal skeleton, the deposited layer, and oxygen in the air exist simultaneously. This position can be called a three-phase active site. The flexible metal skeleton and the deposited layer form a contact layer 2 by chemical bonding at the three-phase point, thereby effectively improving the bonding force between the flexible metal skeleton and the deposited layer. In addition, the flexible metal skeleton and the deposited layer undergo an in-situ oxidation reaction, which increases the bonding force between the contact layer 2 and the air electrode 1 and the connector 3, respectively, thereby achieving a good bonding of the contact layer 2, the air electrode 1, and the connector 3, and further improving the stability of the overall structure.
[0068] By adopting the above technical scheme, the present invention generates a spinel structure by an oxidation reaction between the flexible metal skeleton and the deposited layer in an atmosphere containing oxygen and under a heating state. Among them, since the oxidation reaction of the flexible metal skeleton and the deposited layer occurs at the three-phase active site, it is inevitable that part of the flexible metal skeleton itself is exposed to the air and oxidized, but there is no need to worry about whether the oxidation problem will cause a change in the internal resistance of the battery. This is because the deposited layer of the present invention is coated on the surface of the flexible metal skeleton, and then when the flexible metal skeleton and the deposited layer undergo an oxidation reaction to generate a spinel structure on the surface of the flexible metal skeleton, the spinel structure in the contact layer 2 of the present invention is coated on the surface of the oxidized flexible metal skeleton. Therefore, the contact layer 2 of the present invention is in contact with the air electrode 1 and the connector 3 respectively through the spinel structure and conducts electrons, so that even if part of the flexible metal skeleton in the contact layer 2 of the present invention is inevitably oxidized, the contact layer 2 still maintains good electrical conductivity.
[0069] Compared with the prior art design of coating the spinel structure material on the surface of the flexible metal skeleton by physical adsorption to prepare the contact layer 2, the flexible metal skeleton and the deposited layer of the present invention are chemically bonded to generate the contact layer 2. Therefore, the flexible metal skeleton and the spinel structure in the contact layer 2 obtained by the present invention are more stably combined, so that the contact layer 2 has good stability. As a result, it is also possible to avoid the reduction of the conductivity and mechanical properties of the contact layer 2 due to the shedding of the coating deposited layer, and to avoid further reaction between the flexible metal skeleton and the metal connector after the deposited layer falls off, such as poisoning of the catalyst Cr, which greatly reduces the working capacity of the solid oxide battery.
[0070] Furthermore, the deposited layer in the flexible contact material can undergo an oxidation reaction with the flexible metal skeleton in an atmosphere containing oxygen and in a heated state. That is, the flexible contact material is respectively bonded to the air electrode 1 and the connector 3, and is directly assembled in the solid oxide battery. The deposited layer in the flexible contact material can undergo an in-situ oxidation reaction with the flexible metal skeleton in an atmosphere containing oxygen and in a heated state to generate a spinel structure coated on the surface of the flexible metal skeleton. There is no need to first prepare a spinel structure and then assemble it in a solid oxide battery. Thus, there is no need for additional settings, and the overall structure with a spinel structure can be obtained only during the operation of the solid oxide battery, the preparation process is simple, and the preparation cost is low. In addition, in the process of in-situ generation of the spinel structure, the spinel structure is in closer contact with the air electrode 1 and the connector 3, respectively, thereby achieving a good combination of the contact layer 2, the air electrode 1, and the connector 3. In other words, the overall structure of the present invention composed of the contact layer 2, the air electrode 1 and the connector 3 has good stability.
[0071] Therefore, compared with the setting of coating to prepare the contact layer 2, the present invention not only has good stability of the obtained contact layer 2, but also has good stability of the overall structure. Therefore, the contact layer 2 and the overall structure obtained by the present invention have good high-temperature conductivity and better long-term operation stability. The surface resistance of the overall structure after 20 cooling-heating cycles is ≤50mΩ·cm 2 .
[0072] In some possible embodiments provided by the present invention, the deposited layer also includes one or more of La, Ce and Y. That is, the deposited layer includes not only one or more of iron, cobalt, nickel, copper and manganese, but also one or more of lanthanum, cerium and yttrium. For example, when the flexible metal skeleton is metal Fe and Mn, the deposited layer can be Ni, Co and Y, and the deposited layer and the flexible metal skeleton generate a general formula of (FeMn) x (NiCoY) 3-x O4 spinel structure, 1≤x≤2. As a result, the deposited layer further includes rare earth elements such as lanthanum, cerium and yttrium. Lanthanum, cerium and yttrium all have strong chemical activity, which is conducive to promoting oxidation reaction between the deposited layer and the flexible metal skeleton and generating a more stable spinel structure. It is also conducive to increasing the bonding strength between the spinel structure and the flexible metal skeleton, improving the anti-oxidation ability of the contact layer 2, and thus improving the stability of the contact layer 2.
[0073] In some possible embodiments provided by the present invention, the thickness of the flexible metal skeleton is 50-500 μm. Thus, the connector 3 and the air electrode 1 are in good contact, and the electronic conduction resistance is reduced. If the thickness is too small, the mechanical strength of the flexible metal skeleton is insufficient and cracking is easy to occur; and if the thickness is too large, the resistance of the flexible metal skeleton itself also increases with the thickness.
[0074] In some possible embodiments provided by the present invention, the pore size of the flexible metal skeleton is 40 to 1800 μm, which can also be understood as the pore size of the flexible metal skeleton is 10 to 300 meshes or 10 to 300 ppi. The above pore size range is conducive to increasing the three-phase active sites of the flexible metal skeleton, oxygen and the deposited layer reaction, thereby promoting the oxidation reaction and obtaining a contact layer 2 with a more stable structure. At the same time, since the flexible metal skeleton is a template that makes the contact layer 2 have a micro-nano scale, the deposited layer is coated on the surface of the flexible metal skeleton, and an oxidation reaction occurs in situ, thereby ensuring that the formed contact layer 2 has a suitable porosity, thereby improving the mass transfer capacity of the contact layer 2.
[0075] In some possible embodiments provided by the present invention, the mass of the deposited layer accounts for 1.5-14.0wt% of the total mass of the flexible contact material. That is, the mass of the deposited layer accounts for 1.5-14.0wt% of the sum of the mass of the deposited layer and the mass of the flexible metal skeleton. At this time, the overall structure consisting of the contact layer 2, the air electrode 1 and the connector 3 is connected to the surface resistance test device to form a loop, and a current is passed through, and the constant current density is 500mA / cm 2 , in air atmosphere, after isothermal operation at 850℃ for 300h, after 20 cooling-heating cycles, the surface resistance of the air electrode connection structure is tested to be ≤40mΩ·cm 2 , wherein the cooling-heating is a process of cooling from 850°C to 200°C, then heating from 200°C to 850°C and continuously running at 850°C for 10 hours. When the mass content of the deposited layer is too little, the spinel structure generated by the reaction of the deposited layer and the flexible metal skeleton is insufficient, resulting in poor conductivity. When the mass content of the deposited layer is too much, it may not be possible to generate a spinel structure with the flexible metal skeleton, and the oxidation of the excess deposited layer will hinder the conduction of electrons. Preferably, the mass of the deposited layer accounts for 5-10wt% of the sum of the mass of the deposited layer and the mass of the flexible metal skeleton. This mass content can further ensure that sufficient spinel structure is formed on the surface of the flexible metal skeleton, reduce internal resistance, and improve the conductivity of the contact layer 2; it also avoids excessive deposition, which is conducive to the entry of air and forms more deposited layer-flexible metal skeleton-oxygen three-phase active sites. Thus, the overall structure consisting of the contact layer 2, the air electrode 1 and the connector 3 is connected to the surface resistance test device to form a loop, and a current is passed, and the constant current density is 500mA / cm 2 , in air atmosphere, after isothermal operation at 850℃ for 300h, after 20 cooling-heating cycles, the surface resistance of the air electrode connection structure is ≤32mΩ·cm 2 The cooling-heating process is a process of cooling from 850°C to 200°C, then heating from 200°C to 850°C and continuously running at 850°C for 10 hours.
[0076] In a second aspect, an embodiment of the present invention further discloses a method for preparing a flexible contact material, which is used to prepare the flexible contact material in any embodiment of the first aspect, comprising the following steps:
[0077] Electrodeposition: The flexible metal skeleton is immersed in an electrolyte for electrodeposition to obtain a flexible contact material. In the embodiment of the present invention, electrodeposition refers to the process of electrochemical deposition of metals or alloys from aqueous solutions, non-aqueous solutions or molten salts of their compounds.
[0078] The electrolyte includes an acid salt and water, and the acid salt is an acid salt corresponding to the components of the deposited layer, that is, the deposited layer is dissolved in water in the form of an acid salt to form an electrolyte, for example, an acid salt formed by manganese and an acid radical, or another example, an acid salt formed by cobalt, lanthanum and an acid radical.
[0079] By adopting the above scheme, the deposition layer is coated on the surface of the flexible metal skeleton by electrodeposition, which is conducive to regulating the deposition amount and uniformity of the deposition layer, promoting the formation of three-phase active sites, and then conducive to the formation of a uniform and appropriate amount of spinel structure on the surface of the flexible metal skeleton, and can ensure that the deposition layer and the flexible metal skeleton have a strong bond, thereby improving the overall stability of the flexible contact material. By the deposition layer being in the form of an acid salt, the components of the deposition layer are promoted to be present in the electrolyte in the form of ions, which can ensure the smooth progress of electrodeposition. The method has simple steps, only requires the preparation of the electrolyte, is simple and easy to operate, has low equipment requirements, low raw material costs, and high utilization rates. It is convenient for assembly line operation and batch manufacturing, and can prepare contact layer reserves in advance for large-scale commercial SOFC stack production, and has broad application prospects.
[0080] The acid salt may include an acid ion, which may be a sulfate or chloride ion, and the corresponding deposited layer is dissolved in water in the form of a sulfate or chloride salt to form an electrolyte. The acid salt formed by the sulfate or chloride ion can provide a stable ion environment during the electrodeposition process, which is conducive to the uniform deposition of metal or alloy ions on the flexible metal skeleton, and can ensure the close bonding between the deposited layer and the flexible metal skeleton.
[0081] Further, the electrolyte also includes a second acid salt, the second acid salt has the same acid radical ions as the acid salt, and the cation in the second acid salt is an alkali metal ion. The second acid salt has the same acid radical ions as the acid salt, and the introduction of other impurities is also avoided. The second acid salt is, for example, sodium sulfate, sodium chloride, potassium sulfate or potassium chloride, which improves the conductivity of the electrolyte, thereby accelerating the electrodeposition process. High conductivity also means that a more uniform ion distribution can be provided, which helps to form a more uniform and dense deposition layer, which is conducive to ensuring long-term stable operation.
[0082] Furthermore, the electrolyte also includes an additive, which is one of pyrophosphate, citrate, ammonium sulfate or boric acid, and can complex with cations to improve deposition quality.
[0083] Preferably, the electrolyte is an acidic solution, and the pH value of the electrolyte is 4 to 7. Specifically, the pH value can be adjusted by adding acid to the electrolyte, such as dilute sulfuric acid and dilute hydrochloric acid, to avoid the introduction of other impurities. Neutral and slightly acidic electrolytes are conducive to the metals in the deposited layer to exist in the electrolyte in the form of ions.
[0084] In some possible embodiments provided by the present invention, in the preparation method of the flexible contact material, a deposition layer is grown on the surface of the flexible metal skeleton by an electrodeposition method, including: preparing an electrolyte, selecting a platinum sheet, graphite, glassy carbon or a soluble metal electrode as an anode, selecting a flexible metal skeleton as a cathode, using a constant voltage, constant current, pulse voltage or pulse current charging mode in the electrolytic cell to obtain a flexible contact material, and removing the flexible contact material from the electrolytic cell, washing, and drying. Before using the flexible metal skeleton as a cathode, ethanol and acetone can be used for ultrasonic cleaning in sequence for 1 to 10 minutes to remove pollutants on the surface of the raw material; the cleaning can be performed by multiple immersion cleaning with deionized water, 3 to 10 times of cleaning, and each cleaning time is 1 to 10 minutes; the drying oven can be set to a drying temperature of 60 to 200°C and a drying time of 1 to 24 hours.
[0085] Furthermore, in the electrodeposition step, the electrodeposition is pulse electrodeposition, and the pulse current density of the pulse electrodeposition is 10 to 100 mA / cm 2 , the pulse frequency is 1 to 100 Hz, the deposition time is 1 to 60 min, and the duty cycle is 20 to 80%. Among them, the pulse frequency reflects the sum of a pulse on time and a pulse off time, that is, the total time. For example, the total time corresponding to a pulse frequency of 1 to 100 Hz is 10ms to 1000ms. The duty cycle refers to the proportion of the pulse on time to the total time. Therefore, by adopting the method of pulse current for electrodeposition and setting it to the above range, a more uniform deposition layer can be formed on the surface of the flexible metal skeleton. Preferably, the pulse off time is 10 to 60 ms. If the pulse current density is too low and the pulse off time is too long, the deposition layer will be redissolved into the electrolyte when there is no current at the cathode, which will lead to insufficient mass content of the deposition layer. Therefore, by setting the above-mentioned pulse current mode and coordinating the control of the pulse off time to the above range, a uniform deposition layer with appropriate deposition amount can be obtained, further enhancing the long-term operation stability of the flexible contact material, so that it can withstand thermal stress and mechanical stress during battery operation.
[0086] Thirdly, combining Figure 1 As shown, the embodiment of the present invention discloses an air electrode connection structure 0 for a solid oxide battery, comprising an air electrode 1, a contact layer 2 and a connector 3 arranged in sequence, wherein the contact layer 2 is a flexible contact material as in any embodiment of the first aspect, and is obtained by an oxidation reaction, wherein the oxidation reaction is a deposition layer and a flexible metal skeleton in an atmosphere containing oxygen and in a heating state to generate a general formula A x B 3-x A spinel structure of O4 (1≤x≤2) is coated on the surface of a flexible metal skeleton, wherein A is a component of the flexible metal skeleton, B is a component of a deposition layer, and 1≤x≤2.
[0087] By adopting the above technical scheme, the flexible contact material can be directly clamped between the connector 3 and the air electrode 1, and the flexible metal skeleton and the deposited layer undergo an in-situ oxidation reaction to obtain the contact layer 2, thereby obtaining the air electrode connection structure 0. The contact layer 2 can form a closer and better interface contact with the connector 3 and the air electrode 1, thereby reducing the surface resistance and improving the conductivity of the battery.
[0088] In any of the above embodiments, the area specific resistance (ASR) of the air electrode connection structure 0 is maintained below 31 mΩ·cm 2 ; After multiple cooling-heating cycles, it can still be lower than 50mΩ·cm 2 , and the growth rate of the surface resistance after 20 cooling-heating cycles is less than 13%, reflecting good performance stability. Furthermore, in some embodiments of the present invention, the surface resistance of the air electrode connection structure 0 will show a downward trend after long-term operation, that is, the conductivity of the air electrode connection structure 0 is further improved after long-term operation. Specifically, after 20 cooling-heating cycles, the reduction rate of the surface resistance of the air electrode connection structure 0 is 10% to 20%. The reduction rate is calculated as (surface resistance before the start of the cycle - surface resistance after the end of the cycle) / surface resistance before the start of the cycle
[0089] In a fourth aspect, an embodiment of the present invention discloses a method for preparing an air electrode connection structure 0, which is used to prepare the air electrode connection structure 0 in any embodiment of the third aspect, comprising the following steps:
[0090] Electrodeposition: The flexible metal skeleton is immersed in an electrolyte for electrodeposition to obtain a flexible contact material; wherein the electrolyte includes an acid salt and water, and the acid salt is an acid salt corresponding to the components of the deposition layer. Specifically, the electrolyte and the acid salt are the same as those in the second aspect above, and will not be described in detail.
[0091] Preparation of air electrode connection structure 0: After assembling the air electrode 1, the flexible contact material and the connector 3, the deposited layer and the flexible metal skeleton undergo oxidation reaction in an atmosphere containing oxygen and in a heated state to obtain the contact layer 2, thereby obtaining the air electrode connection structure 0. The heating temperature of the heated state is 800-1000°C. Specifically, the heated state refers to heating to the oxidation temperature required for the oxidation reaction between the deposited layer and the flexible metal skeleton, that is, the oxidation temperature is 800-1000°C.
[0092] By adopting the above technical scheme, a flexible contact material can be prepared by electrodeposition. The flexible contact material prepared by this method is different from the rigid contact material that is coated with slurry and then sintered firmly. It maintains the flexibility of the metal material before use and can be directly clamped between the connector 3 and the air electrode 1. Then, after the air electrode 1, the flexible contact material and the connector 3 are assembled, the flexible metal skeleton and the deposited layer undergo an in-situ oxidation reaction to prepare the contact layer 2, and the air electrode connection structure 0 is obtained. While achieving good bonding with adjacent components, it exhibits good high-temperature conductivity and long-term operation stability. The preparation method is simple and feasible.
[0093] In this embodiment, in the step of preparing the air electrode connection structure 0, the air electrode, the flexible contact material and the connector are assembled and then sintered, so that the deposited layer and the flexible metal skeleton undergo an oxidation reaction to generate the contact layer 2, thereby obtaining the air electrode connection structure 0. Specifically, the sintering is performed in an oxygen-containing atmosphere, the sintering temperature is 800 to 1000° C., and the sintering time is 2 to 50 hours, which ensures that the oxidation reaction is fully carried out, and the air electrode connection structure 0 with good chemical and mechanical stability can be obtained.
[0094] Specifically, in the embodiment of the present invention, during the preparation of the air electrode connection structure 0, the air electrode connection structure 0 is specifically configured as follows: Figure 1 The sandwich structure shown has a contact layer 2 in the middle and air electrodes 1 and connectors 3 on both sides. A collector sheet sintered with an air electrode thin layer is usually used as the air electrode 1, and the air electrode thin layer and the collector sheet are commonly used air electrode materials for SOFC (such as LSM, LSC and LSCF); a metal connector coated with a coating is used as the connector 3. Among them, the coating can be a spinel coating or a perovskite coating. Specifically, the above sandwich structure is fixed with a high-temperature resistant clamp and a certain external pressure is applied to ensure that the layers are in close contact. Four leads are fixed in groups of two on the air electrode 1 and the connector 3 as current lines and voltage lines, and then sintered in an oxygen atmosphere. The metal skeleton and the deposited layer in the flexible contact material are oxidized to form a spinel structure to obtain an air electrode connection structure 0.
[0095] In another embodiment of the present invention, in the step of preparing the air electrode connection structure 0, the air electrode, the flexible contact material and the connector are assembled to form a solid oxide battery, the solid oxide battery is started and the solid oxide battery is brought to the working temperature, so that the deposited layer and the flexible metal skeleton undergo an oxidation reaction to generate the contact layer 2, and the air electrode connection structure is obtained. Wherein, the working temperature refers to the temperature required for the solid oxide battery to work normally. For SOEC, the working temperature required for SOEC to perform the electrolysis reaction. For SOFC, the working temperature required for SOFC to convert the chemical energy in the fuel into electrical energy. Wherein, the operation process of the solid oxide battery includes: starting the solid oxide battery, turning on the temperature control device to heat the solid oxide battery to the working temperature. Specifically, the battery operating temperature will be greater than or equal to the oxidation temperature required for the deposited layer and the flexible metal skeleton in the flexible contact material to undergo an oxidation reaction. That is to say, in the process of heating the solid oxide battery, the conditions required for the oxidation reaction to occur will be reached first, and then in the process of the solid oxide battery reaching the working temperature, the deposited layer and the flexible metal skeleton will undergo an oxidation reaction to generate the contact layer 2. More specifically, the oxidation temperature is, for example, 800 to 1000°C, and the operating temperature is, for example, 800 to 1000°C.
[0096] The above-mentioned direct assembly into a solid oxide battery, the method of obtaining the air electrode connection structure by opening the battery preparation, and the method of first sintering to obtain the air electrode connection structure 0 and then assembling it into a solid oxide battery, can both obtain a contact layer with a high degree of integration between the spinel structure and the flexible metal skeleton, and can both obtain an air electrode connection structure with a tight integration between the contact layer and the air electrode and the connector, and thus can obtain a solid oxide battery with excellent conductivity and long-term operation stability.
[0097] Furthermore, the above-mentioned direct assembly into a solid oxide battery, by opening the battery, the method of preparing the air electrode connection structure, directly using the solid oxide battery in the process of heating to the working temperature, can obtain the air electrode connection structure 0 with a spinel structure, the preparation process is simple, and the preparation cost is low. In addition, the flexible contact material before the oxidation reaction is more flexible than after the oxidation reaction is completed, so before the oxidation reaction, the air electrode, the flexible contact material and the connector are assembled into the solid oxide battery, and the installation is easier and more convenient. At the same time, this direct assembly method is conducive to a better combination between the contact layer 2, the air electrode 1 and the connector 3, thereby further improving the stability and conductivity of the entire air electrode connection structure 0.
[0098] In other embodiments of the present invention, in the step of preparing the air electrode connection structure 0, the flexible contact material, the connector and the solid oxide battery are assembled into a battery stack, the battery stack is started and the battery stack reaches the operating temperature, so that the deposited layer and the flexible metal skeleton undergo an oxidation reaction to generate a contact layer, and the air electrode connection structure is obtained. Among them, the operating temperature refers to the temperature required for the solid oxide battery to work normally. For SOEC, the operating temperature required for SOEC to perform an electrolysis reaction. For SOFC, the operating temperature required for SOFC to convert chemical energy in the fuel into electrical energy. As a result, the internal resistance of the battery stack is reduced, the energy conversion efficiency is improved, and the preparation method is simple, the production cost is low, and the production efficiency is high.
[0099] It should be noted that, in the embodiment of the present invention, the test method of the high temperature electrical conductivity of the air electrode connection structure 0 is specifically as follows:
[0100] Surface resistance test: constant current four-electrode method was used. At 850℃ and air atmosphere, the air electrode connection structure 0 was connected to the surface resistance test device to form a loop, and current was passed. The constant current density was 500mA / cm 2 .
[0101] Isothermal operation: At a fixed temperature of 850°C and air atmosphere, a constant current density of 500mA / cm 2 , continuous operation for 100h.
[0102] 20 cooling-heating cycle tests: the ambient temperature is cooled from 850℃ to 200℃, then heated from 200℃ to 850℃, and then continuously operated at 850℃ for 10h; then cooled to 200℃ again, then heated from 200℃ to 850℃, and then continuously operated at 850℃ for 10h; this cycle is repeated 20 times. Operation refers to the surface resistance test device maintaining a constant current density of 500mA / cm 2 working status.
[0103] In a fifth aspect, an embodiment of the present invention discloses a solid oxide battery, including an air electrode connection structure as in any embodiment of the third aspect, or an air electrode connection structure obtained by the preparation method as in any embodiment of the fourth aspect. Specifically, the solid oxide battery includes a solid oxide fuel cell and a solid oxide electrolyzer.
[0104] The above technical solution can improve the conductivity between the air electrode and the connector of the solid oxide battery, which is beneficial to improving the long-term stable operation performance and allowing more current to be transmitted under the same voltage, thereby improving the current collection efficiency of the solid oxide battery.
[0105] In a sixth aspect, an embodiment of the present invention discloses a battery stack, comprising a solid oxide battery as in any embodiment of the fifth aspect, wherein the battery stack is formed by stacking a plurality of solid oxide batteries.
[0106] By adopting the above technical solution, the conductivity of adjacent solid oxide cells can be improved, so that more current can be transmitted under the same voltage, thereby improving the current collection efficiency of the battery stack, which is beneficial to improving the operating efficiency and long-term stable operation of the battery stack.
[0107] The following will introduce it through a more specific implementation method.
[0108] The air electrode connection structure 0 of Examples 1-6 is prepared by the following steps:
[0109] Prepare the electrolyte: dissolve the sulfate or chloride corresponding to the components of the deposited layer in deionized water at a dosage not exceeding its room temperature solubility, then add potassium or sodium salt of the same acid ion (such as potassium sulfate, potassium chloride, sodium sulfate or sodium chloride), and then add additives (such as pyrophosphate, citrate, ammonium sulfate or boric acid), adjust the pH of the solution to 4-7 with dilute hydrochloric acid or dilute sulfuric acid, continue stirring for 2-24 hours at a speed of 100-500 rpm until the solution is clear and transparent.
[0110] Electrodeposition: The flexible metal skeleton is ultrasonically cleaned with ethanol and acetone in sequence and used as the cathode. A platinum sheet, graphite, glassy carbon or a soluble metal electrode is selected as the anode. The reaction area of the electrode is immersed in the electrolyte in the electrolytic cell, so that the deposition layer elements in the electrolyte are deposited on the flexible metal skeleton to form a deposition layer. The electrodeposited flexible contact material is soaked and cleaned with deionized water several times. After removing the solution residue, it is dried to obtain the flexible contact material.
[0111] Preparation of air electrode connection structure 0: Cut the flexible contact material into a suitable size for use and place it between the air electrode 1 and the connector 3. The air electrode 1 is sintered with an air electrode thin layer, and the connector 3 is coated with a coating alloy (SUS411), and the coating is a spinel coating. The preparation method of the spinel coating refers to the Chinese patent document CN112323065A. Platinum wire or silver wire is connected to the outside of the air electrode 1 and the connector 3 as a voltage line and a current line, and a pre-tightening pressure is applied through an external clamp to ensure that each part is in contact. The entire pre-tightened clamp, air electrode 1, flexible contact material and connector 3 are sintered at a temperature of 800 to 1000°C in an air atmosphere for 2 to 50 hours to obtain the air electrode connection structure 0.
[0112] The components of the flexible contact materials of the embodiments of the present invention and the comparative examples are shown in Table 1.
[0113] Table 1
[0114] Flexible metal frame Quality content Sedimentary layer Quality content Example 1 Co 99.0 Mn 1.0 Example 2 Cu 98.3 Mn 1.7 Example 3 Cu 93.7 Mn 6.3 Example 4 Cu 91.9 Mn 8.1 Example 5 Cu 87.2 Mn 12.8 Example 6 Cu 85.0 Mn 15.0 Comparative Example Cu 100 / /
[0115] The following provides more specific preparation methods and testing methods for embodiments and comparative examples:
[0116] Example 1
[0117] Prepare electrolyte: weigh 6.29g manganese chloride and 14.92g potassium chloride into a clean beaker, then add 80mL deionized water, stir until all solids are dissolved, then add 2.47g boric acid and stir until dissolved, and make up the volume of the solution to 100mL with deionized water. At this time, the molar concentrations of manganese chloride, potassium chloride and boric acid in the solution are 0.5M, 2M and 0.4M, respectively. Then adjust the pH of the solution to 5 with 1M dilute hydrochloric acid, stir magnetically for 24h at a speed of 300rpm to prepare the electrolyte.
[0118] Electrodeposition: The foamed cobalt with a pore size of 150ppi and a thickness of 100μm was ultrasonically cleaned with ethanol and acetone for 5min each, and then dried. The cleaned foamed cobalt was then fixed with an electrode clamp as the cathode, and a 0.5mm thick manganese sheet was selected as the anode. The electrolyte was poured into the electrolytic cell, and the two electrodes were immersed in the electrolyte face to face, with an immersion area of 1.5cm 2 The pulse current mode was adopted, and the saturated calomel electrode was selected as the reference electrode. The cathode current was set to 90 mA, the pulse on time was 40 ms, the pulse off time was 80 ms, and the pulse current density was 20 mA / cm 2 , the pulse frequency is 8.3 Hz, and the deposition time is 10 min. The electrodeposited cobalt foam is washed with deionized water for 5 times, each time for 2 min, to remove the electrolyte residue, and then dried in an oven at 80°C for 6 h to obtain a flexible contact material as shown in Table 1.
[0119] Preparation of air electrode connection structure 0: Cut a flexible contact material with a diameter of 10 mm and place it between the air electrode 1 and the connector 3. Two platinum wires are sintered on the outside of the air electrode 1 and the connector 3 respectively with platinum paste. The entire test sample is pre-tightened by an external fixture to ensure that all parts are in contact. The entire pre-tightened fixture and sample are sintered at 1000°C for 5 hours in an air atmosphere, so that the flexible metal skeleton and the deposited layer undergo oxidation reaction to obtain the contact layer 2, and the air electrode connection structure 0 is obtained.
[0120] Performance test: The surface resistance of the contact layer 2 was tested using the constant current four-electrode method. The test conditions were 850°C in air atmosphere and a constant current density of 500mA / cm 2 , isothermal operation for 100 h, the test results are shown in Table 2 and Figure 2 shown.
[0121] Example 2
[0122] Preparation of electrolyte: weigh 16.9 g of manganese sulfate monohydrate and 26.15 g of potassium sulfate into a clean beaker, then add 80 mL of deionized water and stir until all the solids are dissolved, then add 5.28 g of ammonium sulfate and stir until dissolved, and make up the volume of the solution to 100 mL with deionized water. At this time, the molar concentrations of manganese sulfate, potassium sulfate and ammonium sulfate in the solution are 1 M, 1.5 M and 0.4 M, respectively. Then adjust the pH of the solution to 4 with 1 M dilute sulfuric acid, stir magnetically for 12 h at a speed of 200 rpm to prepare the electrolyte.
[0123] Electrodeposition: The copper foam with a pore size of 110ppi and a thickness of 100μm was ultrasonically cleaned with ethanol and acetone for 10min each, and then dried. The cleaned copper foam was then fixed with an electrode clamp as the cathode, and a 0.3mm thick graphite sheet was selected as the anode. The electrolyte was poured into the electrolytic cell, and the two electrodes were immersed in the electrolyte face to face, with an immersion area of 1.5cm 2 , using the constant voltage mode, selecting the saturated calomel electrode as the reference electrode, the cathode voltage was set to 1.64 V, and the deposition time was 5 min. The electrodeposited copper foam was soaked and cleaned with deionized water for 5 times, each time for 2 min to remove the electrolyte residue, and then dried in an oven at 100 ° C for 1 h to obtain the flexible contact material shown in Table 1.
[0124] Preparation of air electrode connection structure 0: Cut a flexible contact material with a diameter of 10 mm and place it between the air electrode 1 and the connector 3. Two platinum wires are sintered on the outside of the air electrode 1 and the connector 3 respectively with platinum paste. The entire test sample is pre-tightened by an external fixture to ensure that all parts are in contact. The entire pre-tightened fixture and sample are sintered at 900°C for 10 hours in an air atmosphere, so that the flexible metal skeleton and the deposited layer undergo oxidation reaction to obtain the contact layer 2, and the air electrode connection structure 0 is obtained.
[0125] Performance test: The surface resistance of the air electrode connection structure 0 was tested using the constant current four-electrode method. The test conditions were 850°C air atmosphere and a constant current density of 500mA / cm 2 , isothermal operation for 100 h, the test results are shown in Table 2 and Figure 2 shown.
[0126] like Figure 3-Figure 4 As shown, the black manganese deposition layer is evenly coated on the surface of the foam copper.
[0127] Example 3
[0128] Prepare the electrolyte: weigh 16.9 g of manganese sulfate monohydrate and 26.15 g of potassium sulfate into a clean beaker, then add 80 mL of deionized water and stir until all the solids are dissolved, then add 2.64 g of ammonium sulfate and stir until dissolved, and make up the volume of the solution to 100 mL with deionized water. At this time, the molar concentrations of manganese sulfate, potassium sulfate and ammonium sulfate in the solution are 1 M, 1.5 M and 0.2 M, respectively. Then adjust the pH of the solution to 4.5 with 1 M dilute sulfuric acid, stir magnetically for 24 hours at a speed of 300 rpm to prepare the electrolyte.
[0129] Electrodeposition: An oxygen-free copper mesh with a pore size of 300 mesh and a thickness of 90 μm was ultrasonically cleaned with ethanol and acetone for 5 min each, and then dried. The cleaned copper mesh was then fixed with an electrode clamp as the cathode, and a 0.5 mm thick manganese sheet was selected as the anode. The electrolyte was poured into the electrolytic cell, and the two electrodes were immersed in the electrolyte face to face, with an immersion area of 1.5 cm 2 The pulse current mode was adopted, and the saturated calomel electrode was selected as the reference electrode. The cathode current was set to 100 mA, the pulse on time was 36 ms, the pulse off time was 24 ms, and the pulse current density was 40 mA / cm 2 , the pulse frequency is 16.7 Hz, and the deposition time is 10 min. The copper mesh after electrodeposition was soaked and cleaned with deionized water for 3 times, each time for 1 min, to remove the electrolyte residue, and then dried in an oven at 60°C for 12 h to obtain a flexible contact material as shown in Table 1.
[0130] Preparation of air electrode connection structure 0: Cut a flexible contact material with a diameter of 10 mm and place it between the air electrode 1 and the connector 3. Two platinum wires are sintered on the outside of the air electrode 1 and the connector 3 respectively with platinum paste. The entire test sample is pre-tightened by an external fixture to ensure that all parts are in contact. The entire pre-tightened fixture and sample are sintered at 950°C for 5 hours in an air atmosphere, so that the flexible metal skeleton and the deposited layer undergo oxidation reaction to obtain the contact layer 2, and the air electrode connection structure 0 is obtained.
[0131] Performance test: The surface resistance of the air electrode connection structure 0 was tested using the constant current four-electrode method. The test conditions were 850°C air atmosphere and a constant current density of 500mA / cm 2 , isothermal operation for 100 h, the test results are shown in Table 2 and Figure 2 shown.
[0132] like Figure 5-Figure 6 As shown, after the manganese layer deposited on the surface of the copper mesh is sintered in an air atmosphere, the generated octahedral spinel structure is obviously coated on the surface of the skeleton, thereby improving the conductive performance of the contact layer 2.
[0133] Example 4
[0134] Prepare electrolyte: weigh 12.58g manganese chloride and 14.92g potassium chloride into a clean beaker, then add 80mL deionized water, stir until all solids are dissolved, then add 2.47g boric acid and stir until dissolved, and make up the volume of the solution to 100mL with deionized water. At this time, the molar concentrations of manganese chloride, potassium chloride and boric acid in the solution are 1M, 2M and 0.4M, respectively. Then adjust the pH of the solution to 4.5 with 1M dilute hydrochloric acid, stir magnetically for 24h at a speed of 300rpm to prepare the electrolyte.
[0135] Electrodeposition: An oxygen-free copper mesh with a pore size of 300 mesh and a thickness of 90 μm was ultrasonically cleaned with ethanol and acetone for 5 min each, and then dried. The cleaned copper mesh was then fixed with an electrode clamp as the cathode, and a 0.5 mm thick manganese sheet was selected as the anode. The electrolyte was poured into the electrolytic cell, and the two electrodes were immersed in the electrolyte face to face, with an immersion area of 1.5 cm 2 The pulse current mode was adopted, and the saturated calomel electrode was selected as the reference electrode. The cathode current was set to 100 mA, the pulse on time was 18 ms, the pulse off time was 12 ms, and the pulse current density was 40 mA / cm 2 , the pulse frequency is 33.3 Hz, and the deposition time is 15 min. The copper mesh after electrodeposition was soaked and cleaned with deionized water for 3 times, each time for 1 min, to remove the electrolyte residue, and then dried in an oven at 80°C for 6 h to obtain a flexible contact material as shown in Table 1.
[0136] Preparation of air electrode connection structure 0: Cut a flexible contact material with a diameter of 10 mm and place it between the air electrode 1 and the connector 3. Two platinum wires are sintered on the outside of the air electrode 1 and the connector 3 respectively with platinum paste. The entire test sample is pre-tightened by an external fixture to ensure that all parts are in contact. The entire pre-tightened fixture and sample are sintered at 950°C for 5 hours in an air atmosphere, so that the flexible metal skeleton and the deposited layer undergo oxidation reaction to obtain the contact layer 2, and the air electrode connection structure 0 is obtained.
[0137] Performance test: The surface resistance of the air electrode connection structure 0 was tested using the constant current four-electrode method. The test conditions were 850°C air atmosphere and a constant current density of 500mA / cm 2 , isothermally run for 300h, then the ambient temperature is cooled from 850℃ to 200℃, then heated from 200℃ to 850℃, and then continuously run at 850℃ for 10h; then cooled to 200℃ again, then heated from 200℃ to 850℃, and then continuously run at 850℃ for 10h; this cycle is repeated 20 times, and the total running time exceeds 700h. The test results are shown in Table 2, Table 3, Figure 2 and Figure 7 shown.
[0138] Example 5
[0139] Prepare electrolyte: weigh 12.58g manganese chloride and 14.92g potassium chloride into a clean beaker, then add 80mL deionized water, stir until all solids are dissolved, then add 3.71g boric acid and stir until dissolved, and make the solution volume 100mL with deionized water. At this time, the molar concentrations of manganese chloride, potassium chloride and boric acid in the solution are 1M, 2M and 0.6M, respectively. Then adjust the pH of the solution to 5.5 with 1M dilute hydrochloric acid, stir magnetically for 24h at a speed of 500rpm to prepare the electrolyte.
[0140] Electrodeposition: The copper foam with a pore size of 110ppi and a thickness of 100μm was ultrasonically cleaned with ethanol and acetone for 5min each, and then dried. The cleaned copper foam was then fixed with an electrode clamp as the cathode, and a 0.1mm thick platinum sheet was selected as the anode. The electrolyte was poured into the electrolytic cell, and the two electrodes were immersed in the electrolyte face to face, with an immersion area of 1.5cm 2 The pulse current mode was adopted, and the saturated calomel electrode was selected as the reference electrode. The cathode current was set to 90 mA, the opening was 40 ms, the closing was 20 ms, and the current density was 40 mA / cm 2 , the pulse frequency is 16.7 Hz, and the deposition time is 20 min. The electrodeposited copper foam is washed with deionized water for 5 times, each time for 3 min, to remove the electrolyte residue, and then dried in an oven at 80°C for 24 h to obtain a flexible contact material as shown in Table 1.
[0141] Preparation of air electrode connection structure 0: Cut a flexible contact material with a diameter of 10 mm and place it between the air electrode 1 and the connector 3. Two platinum wires are sintered on the outside of the air electrode 1 and the connector 3 respectively with platinum paste. The entire test sample is pre-tightened by an external fixture to ensure that all parts are in contact. The entire pre-tightened fixture and sample are sintered at 950°C for 10 hours in an air atmosphere, so that the flexible metal skeleton and the deposited layer undergo oxidation reaction to obtain the contact layer 2, and the air electrode connection structure 0 is obtained.
[0142] Performance test: The surface resistance of the air electrode connection structure 0 was tested using the constant current four-electrode method. The test conditions were 850°C air atmosphere and a constant current density of 500mA / cm 2 , isothermal operation for 300h. Then the ambient temperature is cooled from 850℃ to 200℃, then heated from 200℃ to 850℃, and then continuously operated at 850℃ for 10h; then cooled to 200℃ again, then heated from 200℃ to 850℃, and then continuously operated at 850℃ for 10h; this cycle is repeated 20 times, and the total operating time exceeds 700h. The test results are shown in Table 2, Table 3, Figure 2 and Figure 7 shown.
[0143] Example 6
[0144] Prepare electrolyte: weigh 12.58g manganese chloride and 14.92g potassium chloride into a clean beaker, then add 80mL deionized water, stir until all solids are dissolved, then add 3.09g boric acid and stir until dissolved, and make up the volume of the solution to 100mL with deionized water. At this time, the molar concentrations of manganese chloride, potassium chloride and boric acid in the solution are 1M, 2M and 0.5M, respectively. Then adjust the pH of the solution to 5 with 1M dilute hydrochloric acid, stir magnetically for 12h at a speed of 300rpm to prepare the electrolyte.
[0145] Electrodeposition: An oxygen-free copper mesh with a pore size of 300 mesh and a thickness of 90 μm was ultrasonically cleaned with ethanol and acetone for 5 min each, and then dried. The cleaned copper mesh was then fixed with an electrode clamp as the cathode, and a 0.5 mm thick manganese sheet was selected as the anode. The electrolyte was poured into the electrolytic cell, and the two electrodes were immersed in the electrolyte face to face, with an immersion area of 1.5 cm 2 The constant current mode was adopted, and the saturated calomel electrode was selected as the reference electrode. The cathode current was set to 75 mA and the current density was 50 mA / cm 2 The electrodeposited copper mesh was washed and soaked in deionized water for 3 times, each time for 2 minutes, to remove the electrolyte residue, and then dried in an oven at 80°C for 12 hours to obtain a flexible contact material as shown in Table 1.
[0146] Preparation of air electrode connection structure 0: Cut a flexible contact material with a diameter of 10 mm and place it between the air electrode 1 and the connector 3. Two platinum wires are sintered on the outside of the air electrode 1 and the connector 3 respectively with platinum paste. The entire test sample is pre-tightened by an external fixture to ensure that all parts are in contact. The entire pre-tightened fixture and sample are sintered at 900°C for 20 hours in an air atmosphere, so that the flexible metal skeleton and the deposited layer undergo oxidation reaction to obtain the contact layer 2, and the air electrode connection structure 0 is obtained.
[0147] Performance test: The surface resistance of the air electrode connection structure 0 was tested using the constant current four-electrode method. The test conditions were 850°C air atmosphere and a constant current density of 500mA / cm 2 , isothermal operation for 100 h, the test results are shown in Table 2 and Figure 2 shown.
[0148] Example 7
[0149] Prepare electrolyte: weigh 12.58g manganese chloride and 14.92g potassium chloride into a clean beaker, then add 80mL deionized water, stir until all solids are dissolved, then add 2.47g boric acid and stir until dissolved, and make up the volume of the solution to 100mL with deionized water. At this time, the molar concentrations of manganese chloride, potassium chloride and boric acid in the solution are 1M, 2M and 0.4M, respectively. Then adjust the pH of the solution to 4.5 with 1M dilute hydrochloric acid, stir magnetically for 24h at a speed of 300rpm to prepare the electrolyte.
[0150] Electrodeposition: An oxygen-free copper mesh with a pore size of 300 mesh and a thickness of 90 μm was ultrasonically cleaned with ethanol and acetone for 5 min each, and then dried. The cleaned copper mesh was then fixed with an electrode clamp as the cathode, and a 0.5 mm thick manganese sheet was selected as the anode. The electrolyte was poured into the electrolytic cell, and the two electrodes were immersed in the electrolyte face to face, with an immersion area of 20 cm 2 The pulse current mode was adopted, and the saturated calomel electrode was selected as the reference electrode. The cathode current was set to 500 mA, the pulse on time was 18 ms, the pulse off time was 12 ms, and the pulse current density was 15 mA / cm 2 , the pulse frequency is 33.3 Hz, and the deposition time is 40 min. The copper mesh after electrodeposition was soaked and cleaned with deionized water for 3 times, each time for 1 min, to remove the electrolyte residue, and then dried in an oven at 80°C for 6 h to obtain a flexible contact material as shown in Table 1.
[0151] Preparation of air electrode connection structure 0: Cut a flexible contact material with an area of 4 cm×4 cm and place it between the air electrode and the connector of adjacent electrolyte-supported solid oxide batteries, assemble it into a battery stack, start the battery stack and allow the battery stack to reach an operating temperature of 850°C, so that the flexible metal skeleton and the deposited layer undergo an oxidation reaction to generate a contact layer 2, thereby obtaining the air electrode connection structure 0.
[0152] Performance test: The battery stack is tested for ohmic resistance and peak power density. The test results are as follows: Fig.10 and Fig.11 shown.
[0153] like Fig.10 As shown, in the process of heating up the battery stack in Example 7, the deposited layer and the flexible metal skeleton undergo oxidation reaction in an air atmosphere to form a contact layer 2. The overall ohmic resistance including the connector, the contact layer and the battery is less than 500 mΩ·cm 2 ( Fig.10 and Z" = 0). Fig.11 As can be seen in the figure, "Current Density" represents current density, "Voltage" refers to voltage, and "Power Density" represents power density. The peak power density can reach 400mW / cm2 The overall ohmic resistance and peak power density can reach the advanced level in the industry.
[0154] Comparative Example
[0155] The copper foam with a pore size of 110ppi and a thickness of 100μm was ultrasonically cleaned with ethanol and acetone for 10min each, and then dried. A copper foam with a diameter of 10mm was cut and placed between the air electrode 1 and the connector 3. Two platinum wires were sintered on the outside of the air electrode 1 and the connector 3 with platinum slurry. The entire test sample was pre-tightened by an external fixture to ensure that all parts were in contact. The entire pre-tightened fixture and sample were sintered at 900℃ for 2h in an oxygen atmosphere to obtain a comparative example.
[0156] Performance test: The surface resistance of the comparative example was tested by the constant current four-electrode method. The test conditions were 850℃ in air atmosphere and constant current density of 500mA / cm 2 , isothermal operation for 100 h, the test results are shown in Table 2 and Figure 2 shown.
[0157] Table 2 ASR changes within 100 hours in the examples and comparative examples
[0158] 0h 100h Rate of change Example 1 30.2 27.2 -9.9% Example 2 27.1 25.2 -7.0% Example 3 24.1 23.5 -2.5% Example 4 23.2 22.6 -2.6% Example 5 23.4 24.3 3.8% Example 6 26.2 30.1 14.9% Comparative Example 41.9 45.4 8.4%
[0159] Table 3 ASR changes of Example 4 and Example 5
[0160] 0h 300h Loop Start End of loop Example 4 23.2 21.0 23.3 19.4 Example 5 23.4 26.5 28.8 32.4
[0161] From Table 2, Table 3, Figure 2 , Figure 7 and Figure 8 The following can be known:
[0162] The ASR of the comparative example was reduced from 41.9 mΩ·cm within 100 h. 2 Increased to 45.4 mΩ·cm 2 , indicating that the conductivity of pure copper metal material in a high temperature oxidizing atmosphere is not particularly excellent, and may continue to decay over a longer period of time. The embodiment of the present invention has a smaller surface resistance than the comparative example.
[0163] Example 1: ASR from 30.2 mΩ·cm within 100 h 2 Reduced to 27.2 mΩ·cm 2 As shown in Table 1, compared with other embodiments, the mass of the manganese deposition layer deposited on the surface of the foamed cobalt in Embodiment 1 is less, and the relative mass ratio of manganese to cobalt is 1%.
[0164] Example 2: ASR from 27.1 mΩ·cm within 100 h 2 Slowly decrease to 25.2mΩ·cm2 In Example 2, the conductivity of the contact layer obtained by sintering the flexible contact material of foam copper deposited with manganese in a high-temperature oxidizing atmosphere is significantly better than the conductivity of the contact layer obtained by oxidizing the pure copper material.
[0165] Example 3: ASR from 24.1 mΩ·cm within 100 h 2 Slowly decrease to 23.5mΩ·cm 2 . Combined Figure 5 and Figure 6 As shown, Example 3 adopts a pulse electrodeposition method, and Example 3 further satisfies the pulse off time of 10 to 60 ms, so that the manganese deposition layer deposited on the surface of the copper mesh is uniform and dense, and the contact layer 2 after sintering has a complete structure, and copper and manganese can be observed to react to form an octahedral spinel structure on the surface.
[0166] Example 4: ASR from 23.2 mΩ·cm within 100 h 2 Slowly decrease to 22.6mΩ·cm 2 . Combined Figure 7 As shown in the figure, the ASR curve of long-term operation shows that each hot and cold cycle will have a certain impact on the surface resistance, but by stabilizing at 850℃ for 10h, the overall resistance level can be reduced. During the operation time of more than 700h, the ASR of Example 4 increased from the initial 23.2mΩ·cm 2 Reduced to 19.4 mΩ·cm 2 That is, the surface resistance of Example 4 after 20 cooling-heating cycles within 700 hours of operation is ≤20 mΩ·cm 2 , which is the most preferred example of this patent. Take an X-ray diffraction pattern (XRD) of the tested sample, such as Figure 8 As shown in the figure, "Intensity" refers to the intensity, and "2-Theta" refers to the 2θ diffraction angle, that is, the angle between the extended line of the incident X-ray and the reflected X-ray. The copper part of the flexible metal skeleton located in the inner layer is oxidized to copper oxide, and the manganese in the outer deposition layer completely reacts with the copper in the flexible metal skeleton to form a copper-manganese spinel phase with higher conductivity.
[0167] Example 5: ASR from 23.4 mΩ·cm within 100 h 2 Slightly increased to 24.3mΩ·cm 2 As shown in Table 1, the mass of the manganese deposited layer deposited on the surface of the copper foam is relatively large, and the relative mass ratio of manganese to copper exceeds 10%. Figure 7 As shown in the figure, the ASR of Example 5 increased from the initial 23.4 mΩ·cm to 2 Increased to 32.4 mΩ·cm 2That is, the surface resistance of Example 5 after 20 cooling-heating cycles within 700 hours of operation is ≤40 mΩ·cm 2 , and still meets the requirements for use as the contact layer between the air electrode and the connector.
[0168] Example 6: ASR from 26.2 mΩ·cm within 100 h 2 Increased to 30.1mΩ·cm 2 (like Figure 2 As shown in Table 1, the mass of the manganese deposition layer deposited on the surface of the copper mesh is relatively large, and the relative mass ratio of manganese to copper reaches 15%. Fig. 9 As shown, the XRD results show that the manganese in the outer deposited layer not only reacts with the copper in the flexible metal skeleton to form a copper-manganese spinel phase, but the excess manganese also generates manganese oxides with greater resistance, indicating that too large a mass fraction of the deposited layer is not conducive to complete reaction to form a spinel phase.
[0169] In addition, since Examples 3 and 4 further satisfy the requirement that the mass of the deposited layer accounts for 5-10wt% of the sum of the mass of the deposited layer and the mass of the flexible metal skeleton, they have a smaller surface resistance. It can be seen from the above that the ASR of Example 4 of the present invention shows a downward trend within 100 hours of isothermal operation at 850°C, and after 300 hours of isothermal operation at 850°C, the surface resistance after 20 cycles of cooling-heating is ≤20mΩ·cm 2 That is, within the total operation time of more than 700 hours, the surface resistance after running for more than 700 hours is reduced by more than 15% compared with the surface resistance at 0 hours. In other words, compared with 0 hours, the conductive performance of Example 4 is further improved after running for more than 700 hours.
[0170] In summary, the flexible contact material of the present invention itself has good electrical conductivity, good chemical stability, tolerance to high temperature oxidizing atmosphere, good chemical compatibility with adjacent materials, and suitable contact area with the connector and the air electrode, as well as low contact resistance. In addition, the thermal expansion coefficient of the flexible contact material matches that of the adjacent materials, has a certain flexibility, can adjust small strains, is low in cost, and has abundant and readily available raw materials. In particular, the preparation process of the flexible contact material of the present invention is also simple. And the contact layer 2 and the overall structure obtained by the present invention have good high temperature conductivity while having better long-term operation stability.
[0171] Although the present invention has been illustrated and described with reference to certain preferred embodiments of the present invention, it should be understood by those skilled in the art that the above is a further detailed description of the present invention in conjunction with specific embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. Those skilled in the art may make various changes in form and details, including making several simple deductions or substitutions, without departing from the spirit and scope of the present invention.
Claims
1. A flexible contact material used between the air electrode and the connector of a solid oxide battery, characterized in that: It includes a flexible metal skeleton and a deposition layer, wherein: The flexible metal skeleton is selected from one or more of Fe, Co, Ni, Cu and Mn, the deposited layer is coated on the surface of the flexible metal skeleton, the deposited layer includes one or more of Fe, Co, Ni, Cu and Mn, the composition of the flexible metal skeleton and the composition of the deposited layer are not completely the same, the deposited layer in the flexible contact material can be oxidized with the flexible metal skeleton in an atmosphere containing oxygen and in a heated state to generate a general formula A x B 3-x O4 (1≤x≤2) spinel structure, the spinel structure is coated on the surface of the flexible metal skeleton, wherein A is the component of the flexible metal skeleton, B is the component of the deposition layer, and 1≤x≤2.
2. The flexible contact material according to claim 1, characterized in that: The deposited layer also includes one or more of La, Ce and Y.
3. The flexible contact material according to claim 1, characterized in that: The thickness of the flexible metal skeleton is 50-500 μm.
4. The flexible contact material according to claim 3, characterized in that: The pore size of the flexible metal skeleton is 40 to 1800 μm.
5. The flexible contact material according to claim 1, characterized in that: The mass of the deposited layer accounts for 5-10 wt % of the total mass of the flexible contact material.
6. A method for preparing a flexible contact material, characterized in that: The method for preparing the flexible contact material according to any one of claims 1 to 5 comprises the following steps: Electrodeposition: immersing the flexible metal skeleton in an electrolyte for electrodeposition to obtain the flexible contact material; Wherein, the electrolyte includes an acid salt and water, and the acid salt is an acid salt corresponding to the components of the deposition layer.
7. The method for preparing the flexible contact material according to claim 6, characterized in that: The acid salt includes an acid ion, and the acid ion is a sulfate ion or a chloride ion.
8. The method for preparing the flexible contact material according to claim 7, characterized in that: The electrolyte further includes a second acid salt, the second acid salt has the same acid radical ion as the acid salt, and the cation in the second acid salt is an alkali metal ion.
9. The method for preparing the flexible contact material according to claim 6, characterized in that: The electrolyte further comprises an additive, wherein the additive is one of pyrophosphate, citrate, ammonium sulfate or boric acid.
10. The method for preparing the flexible contact material according to claim 6, characterized in that: The pH value of the electrolyte is 4-7.
11. The method for preparing the flexible contact material according to claim 6, characterized in that: In the electrodeposition step, the electrodeposition is pulse electrodeposition, and the pulse current density of the pulse electrodeposition is 10 to 100 mA / cm 2 , the pulse frequency is 1 to 100 Hz, the deposition time is 1 to 60 minutes, and the duty cycle is 20 to 80%.
12. An air electrode connection structure for a solid oxide battery, characterized in that: The invention comprises an air electrode, a contact layer and a connector arranged in sequence, wherein the contact layer is obtained by an oxidation reaction of the flexible contact material according to any one of claims 1 to 5, wherein the oxidation reaction is that the deposited layer reacts with the flexible metal skeleton under an atmosphere containing oxygen and under a heating state to generate a general formula A x B 3-x O4 (1≤x≤2) spinel structure, the spinel structure is coated on the surface of the flexible metal skeleton, wherein A is the component of the flexible metal skeleton, B is the component of the deposition layer, and 1≤x≤2.
13. The air electrode connection structure according to claim 12, characterized in that: The air electrode connection structure is connected to the surface resistance test device to form a loop, and current is passed through the loop with a constant current density of 500 mA / cm 2 , in air atmosphere, after isothermal operation at 850°C for 300h, after 20 cooling-heating cycles, the surface resistance of the air electrode connection structure is tested to be ≤50mΩ·cm 2 , wherein the cooling-heating is a process of cooling from 850°C to 200°C, then heating from 200°C to 850°C and continuously operating at 850°C for 10 hours.
14. A method for preparing an air electrode connection structure, characterized in that: The method for preparing the air electrode connection structure as claimed in claim 12 comprises the following steps: Electrodeposition: immersing the flexible metal skeleton in an electrolyte for electrodeposition to obtain the flexible contact material; Preparing an air electrode connection structure: after assembling the air electrode, the flexible contact material and the connector, the deposited layer and the flexible metal skeleton undergo an oxidation reaction under an oxygen-containing atmosphere and a heating state to obtain the contact layer, thereby obtaining the air electrode connection structure; Wherein, the electrolyte includes an acid salt and water, and the acid salt is an acid salt corresponding to the components of the deposition layer.
15. The method for preparing the air electrode connection structure according to claim 14, characterized in that: The heating temperature of the heating state is 800-1000°C.
16. The method for preparing the air electrode connection structure according to claim 14, characterized in that: In the step of preparing the air electrode connection structure, the air electrode, the flexible contact material and the connector are assembled and then sintered so that the deposited layer and the flexible metal skeleton undergo an oxidation reaction to generate the contact layer, thereby obtaining the air electrode connection structure.
17. The method for preparing the air electrode connection structure according to claim 14, characterized in that: In the step of preparing the air electrode connection structure, the air electrode, the flexible contact material and the connector are assembled into a solid oxide battery, the solid oxide battery is started and the solid oxide battery reaches the operating temperature, so that the deposited layer and the flexible metal skeleton undergo an oxidation reaction to generate the contact layer, thereby obtaining the air electrode connection structure.
18. A solid oxide battery, characterized in that: It comprises the air electrode connection structure as described in any one of claims 12-13, or comprises the air electrode connection structure obtained by the preparation method according to any one of claims 14 to 17.
19. A battery stack, characterized in that: Comprising the solid oxide battery as claimed in claim 18.
Citation Information
Patent Citations
High-temperature corrosion-resistant conductive ceramic coating material for solid oxide fuel cell metal connector and preparation method for high-temperature corrosion-resistant conductive ceramic coating material
CN103422090A
Flexible positive electrode of lithium-ion battery, preparation method of flexible positive electrode and super-flexible lithium-ion all-battery
CN106207091A
Electrical contact layer for use in solid oxide fuel cell, method for preparing same, and solid oxide fuel cell comprising same
CN116470089A
A method for the deposition of a film of a manganese / cobalt mixed oxide on a metallic substrate
EP2684977A1
Fabrication method of porous metal oxide foam for cathode current collector of solid oxide fuel cell
KR100797048B1